In vitro generation of mature human osteoclasts. - Hemingway, F; Cheng, X; Knowles, H; Estrada, F; Gordon, S; Athanasou, N (2011)
Mononuclear precursors of human osteoclasts are found in the CD14(+) monocyte fraction of circulating peripheral blood mononuclear cells (PBMCs). It is possible to generate osteoclasts in vitro from PBMCs cultured with macrophage colony-stimulating factor and receptor activator for nuclear factor κB ligand. In these cultures, however, it is not possible to distinguish the effect of a specific agent on osteoclast resorption activity as opposed to osteoclast differentiation. To produce a population of mature human osteoclasts to study osteoclast lacunar resorption specifically, we cultured CD14(+) human monocytes on hydrophobic dishes in order to generate and maintain osteoclasts in suspension prior to culturing them on coverslips and dentine slices. Multinucleated cells formed in these cultures expressed vitronectin receptor, tartrate-resistant acid phosphatase, and cathepsin K. These cells also produced F-actin rings and were capable of extensive lacunar resorption on dentine slices after 24 h in culture. Lacunar resorption was inhibited by calcitonin and zoledronate but not by osteoprotegerin. This method of generating a highly enriched population of mature human osteoclasts should provide a valuable means of specifically assessing the effect of molecular factors (e.g., cytokines, growth factors, hormones) and therapeutic agents on osteoclast resorption activity.